ANALYSIS OF PENSIONER CREDIT GROWTH RATE AT NASARI SAVINGS AND LOAN COOPERATIVE IN LHOKSEUMAWE - Tengku Wulan Handayani; Meutia Sari; Alya Agnes Yulanda; Mira Agustina; Fitri Yusriani; Rico Nur Ilham (PT. Radja Intercontinental Publishing, 2023)
This study aims to determine the growth of pension loans at the Savings and Loans Cooperative in Lhokseumawe. the data obtained or taken is based on the results of interviews conducted at the Nasari Savings and Loans Cooperative in Lhokseumawe using data from 2017 to 2021. The results showed that the growth of pension loans in savings and cooperative loans fluctuated and tended to decline. The author advises the savings and loan cooperative Nasari in Lhokseumawe to reduce the interest rate on pension loans, so that it can compete with other cooperatives and increase credit growth every year.